Abdominal drain straying into right atrium: a case report - Junya Toyoda; Hitoshi Sekido; Kazuhisa Takeda; Tetsuya Shimizu; Goro Matsuda (Surgical Case Reports, 2019)
Abstract Background A drain exchange with the use of a guidewire may be accompanied by serious complications. Case presentation This case involved an 86-year-old man with overlapping cancers of intrahepatic cholangiocarcinoma and perihilar cholangiocarcinoma. A left hepatectomy, a left caudal lobectomy (with a medial hepatic vein preservation), an extrahepatic bile duct resection, and a right hepatojejunostomy were performed. The abdominal drain was placed into the hepatectomy side. Bile leakage occurred on the seventh day after the surgery, and the drain was exchanged. Since the bile leakage was still detectable via a computed tomography (CT) scan on the 15th postoperative day, the drain was exchanged again. On the next day, blood had discharged from the drain. A CT scan revealed that the tip of the drain was straying into the right atrium (RA) and the drain was removed from the inferior vena cava (IVC) under general anesthesia. One week later, a fiburin thrombus was observed from the IVC to the RA via the use of transthoracic echocardiography. A right atrial incision, a thrombus removal, and a middle hepatic vein merging section closure surgery were performed. Afterward, the patient’s general condition gradually improved, and he was transferred to the hospital for rehabilitation. Conclusion More careful guidewire operations are necessary at the time of the exchange of the drain to prevent the drain from being placed too close to blood vessels.